2009
DOI: 10.1128/mcb.00272-09
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Bacterial Rho Factor in Yeast Identifies New Factors Involved in the Functional Interplay between Transcription and mRNP Biogenesis

Abstract: In eukaryotic cells, the nascent pre-mRNA molecule is coated sequentially with a large set of processing and binding proteins that mediate its transformation into an export-competent ribonucleoprotein particle (mRNP) that is ready for translation in the cytoplasm. We have implemented an original assay that monitors the dynamic interplay between transcription and mRNP biogenesis and that allows the screening for new factors linking mRNA synthesis to translation in Saccharomyces cerevisiae. The assay is based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 71 publications
3
40
0
Order By: Relevance
“…Our previous analyses by the Rho-based approach of a subset of commonly-studied yeast transcripts such as PMA1 and PGK1 substantiated the essential role of Rrp6p in the elimination of aberrant mRNPs and revealed the implication of Nrd1p-Nab3p complex in the activation of the QC process. [15][16][17] However, in the course of those studies we noticed that the HXK1 transcript, which is also strongly affected by Rho action, was not rescued from degradation upon alteration of the Nrd1p-Nab3p complex or removal of Rrp6p and its activating cofactors. In the present work, we show that the elimination of Rho-induced aberrant HXK1 mRNPs is in fact mediated by an alternative nuclear QC pathway that relies on the degradation activity of the 5 0 -3 0 exonuclease Rat1p.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Our previous analyses by the Rho-based approach of a subset of commonly-studied yeast transcripts such as PMA1 and PGK1 substantiated the essential role of Rrp6p in the elimination of aberrant mRNPs and revealed the implication of Nrd1p-Nab3p complex in the activation of the QC process. [15][16][17] However, in the course of those studies we noticed that the HXK1 transcript, which is also strongly affected by Rho action, was not rescued from degradation upon alteration of the Nrd1p-Nab3p complex or removal of Rrp6p and its activating cofactors. In the present work, we show that the elimination of Rho-induced aberrant HXK1 mRNPs is in fact mediated by an alternative nuclear QC pathway that relies on the degradation activity of the 5 0 -3 0 exonuclease Rat1p.…”
Section: Discussionmentioning
confidence: 97%
“…In our previous studies, we monitored the effect of Rho activity by measuring the steady-state levels of a set of widely-studied yeast mRNAs (PMA1, PGK1, FBA1 and ACT1) and we found that PMA1 was the most affected with a 60% to 70% reduction, which led us to use it as a model transcript for further characterization of the QC system. 15,16 As shown by Northern blot analysis and RT-qPCR quantifications in Fig. 1, a large drop in the level of PMA1 mRNA is observed under Rho inducing conditions and the absence of the exonuclease Rrp6p in the rrp6D strain restores the PMA1 mRNA to nearly normal level.…”
Section: Hxk1 Transcript Is Affected By Rho Activity Independently Ofmentioning
confidence: 99%
See 3 more Smart Citations